Consistency of noncognitive skills and their relation to educational outcomes in a UK cohort - Tim T. Morris (Nature Publishing Group, 2021)
Abstract Noncognitive skills have been shown to associate with a range of health and socioeconomic outcomes. Many studies have relied on cross sectional data and have been unable to assess the longitudinal consistency of noncognitive skill measures. Using data from a UK birth cohort, we investigated a range of noncognitive skills: behavioural problems, social skills, communication, self-esteem, persistence, locus of control, empathy, impulsivity and personality. We assessed their consistency over a 17-year period throughout childhood and adolescence (age 6 months to 18 years), their genomic architecture, and their associations with socioeconomic outcomes. We found high longitudinal measurement consistency for behavioural and communication skills, but low consistency for other noncognitive skills, suggesting a high noise to signal ratio. We observed consistent non-zero heritability estimates and genetic correlations for only behavioural difficulties. Using aggregate measures of each skill over time, we found evidence of phenotypic correlations and heritability ( $$h_{SNP}^2$$ h S N P 2  = 0.1–0.2) for behaviour, communication, self-esteem and locus of control. Associations between noncognitive skills and educational outcomes were observed for skills measured in mid to late childhood but these were at most a third of the size of IQ-education associations. These results suggest that measures designed to capture noncognitive skills may be subject to considerable response heterogeneity or measurement error. Aggregate measures that leverage repeat responses from longitudinal data may offer researchers more reliable measures that better identify underlying noncognitive skills than cross sectional measures.